Study of Some Hematological Parameters of Dogs Infected with Toxocariasis, before and after the Treatment with Tetramisole, in Al-Diwaniyah Governorate, Iraq - Jarry, Salem; Alfatlawi, MAA (Iraqi Journal of Science, 2023)
The presented investigation, here, was carried out to understand the status of the blood parameters, before and after deworming of Toxocara infection in dogs. For performing the study, 15 pet dogs were recruited from some residential areas in Al-Diwaniyah Province, Iraq. These dogs were exposed to fecal-microscopic based detection of Toxocara eggs and hematological based evaluation of white blood cell (WBC), red blood cell (RBC), and differential counts before and 10 days after treatment with tetramisole. The helminth eggs in the feces of dogs were detected by the flotation method. In case of egg detection, deworming was carried out with tetramisole. The results revealed that the egg number was significantly (p˂0.05) decreased in all age groups (˂2, 2 to ˂4, and ≥4 years old) after using the deworming drug. For the hematological features, WBCs and lymphocytes (LY) were significantly (p˂0.05) decreased, while the granulocytes (GR) and RBCs were significantly (p˂0.05) increased after utilizing the anthelmintic drug. No changes were detected at the levels of hemoglobin (HB) and platelets (PLs) after the use of tetramisole. The results may indicate a strong deworming effect of tetramisole against Toxocara adult worms, that led to decrease the egg counts in the feces of the studied dogs in accompanied with the correction of the hematological picture regarding WBCs, LY, GR, and RBCs.